Obesity in Patients Undergoing Lumbar Degenerative Surgery—A Retrospective Cohort Study of Postoperative Outcomes. Issue 17 (1st September 2021) - Varshneya, Kunal; Wadhwa, Harsh; Stienen, Martin N.; Ho, Allen L.; Medress, Zachary A.; Aikin, Jessica; Li, Gordon; Desai, Atman; Ratliff, John K.; Veeravagu, Anand
Abstract : Study Design: Retrospective cohort studying using a national, administrative database. Objective: The aim of this study was to determine the postoperative complications and quality outcomes of patients with and without obesity undergoing surgical management for lumbar degenerative disease (LDD). Summary of Background Data: Obesity is a global epidemic that negatively impacts health outcomes. Characterizing the effect of obesity on LDD surgery is important given the growing elderly obese population. Methods: This study identified patients with who underwent surgery for LDD between 2007 and 2016. Patients were stratified based on whether the patient had a concurrent diagnosis of obesity at time of surgery. Propensity score matching (PSM) was then utilized to mitigate intergroup differences between patients with and without obesity. Patients who underwent three or more levels surgical correction, were under the age of 18 years, or those with any previous history of trauma or tumor were excluded from this study. Baseline comorbidities, postoperative complication rates, and reoperation rates were determined. Results: A total of 67, 215 patients underwent primary lumbar degenerative surgery, of which 22, 405 (33%) were obese. After propensity score matching, baseline covariates of the two cohorts were similar. The complication rate was 8.3% in the nonobese cohort and 10.4% in the obese cohort ( P  < 0.0001). Patients with obesity also had longer lengths of stay (2.7 days vs. 2.4 days, P  < 0.05), and higher rates of reoperation and readmission at all time-points through the study follow-up period to their nonobese counterparts ( P  < 0.05). Including payments after discharge, lumbar degenerative surgery in patients with obesity was associated with higher payments throughout the 2-year follow-up period ($68, 061 vs. $59, 068 P  < 0.05). Conclusion: Patients with a diagnosis of obesity at time of LDD surgery are at a higher risk for postoperative complications, reoperation, and readmission. Level of Evidence: 4 Abstract : Obesity is a factor that determines outcomes of surgical management for lumbar degenerative disease (LDD). In this study, we demonstrate that patients with obesity had longer lengths of stay, higher rates of postoperative complication, reoperation, and readmission, and higher payments at all time-points through the 2-year follow-up period.